Open Access to research data as a driver for Open science - Giglia, Elena (JLIS.it, 2015)
The two-days conference "Open Access to research data as a driver for Open Science" (Athens, 15-16 January 2015), as the final event of the RECODE project (Policy RECommendations for Open Access to Research Data in Europe) has been a unique occasion to think about Open Access to research data as a way to move towards Open science. High-level speakers and an active audience have discussed on values, risks, opportunities, open issues, best practices; the aim of this paper is to deal with the complexity of these issues and to give a taste of the importance of open data in the near future.